2020
DOI: 10.1177/0021886320973809
|View full text |Cite
|
Sign up to set email alerts
|

When The Dodo Became Extinct: Why Rethinking Change Should Not Take A Pandemic

Abstract: The degree of transformative change occurring in organizations due to the COVID-19 pandemic is extensive, with large-scale downsizing, rightsizing, workplace changes, structural transformation, and a general unease taking place. The sheer scale of these changes has not been seen for a generation. Technically, this situation represents an opportunity for organizational change researchers to dive deep and make sense of what has occurred to organizations globally, particularly because we already have the tools to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Another study found that refined management strategies in non‐isolated areas of a general hospital led to effective COVID‐19 prevention (Xu et al, 2020 ). Healthcare workers learned to work in a redesigned format, were exposed to clinical challenges, acquired additional skills, and faced difficulties, all of which were accompanied by uncertainty, risk of infection, threat of morbidity, and unusual workloads (Schwarz & Bouckenooghe, 2021 ). Indeed, nurse managers in mental health centers reported on the change from a familiar routine to a new reality with family members' and volunteers' visits forbidden, and working in capsules (Kagan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that refined management strategies in non‐isolated areas of a general hospital led to effective COVID‐19 prevention (Xu et al, 2020 ). Healthcare workers learned to work in a redesigned format, were exposed to clinical challenges, acquired additional skills, and faced difficulties, all of which were accompanied by uncertainty, risk of infection, threat of morbidity, and unusual workloads (Schwarz & Bouckenooghe, 2021 ). Indeed, nurse managers in mental health centers reported on the change from a familiar routine to a new reality with family members' and volunteers' visits forbidden, and working in capsules (Kagan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This workforce generation has not experienced organizational changes to the degree triggered by COVID-19 (Schwarz & Bouckenooghe, 2020), which has resulted in stress for these workers (Kniffin et al, 2021). Essentially, workers need support to navigate these changes.…”
Section: Covid-19 Impact: Professional and Personalmentioning
confidence: 99%
“…Evidence abounds about the rare and critical nature of the COVID-19 pandemic. According to the definition of a critical incident or the criteria outlined by Akkermans et al (2018) , COVID-19 deserves research attention for its effects on workers ( Schwarz & Bouckenooghe, 2021 ; Schwarz & Stensaker, 2020 ). Moreover, Hennekam et al (2021 , p. 4) characterized the pandemic as distinct from prior critical events as it was a “multi-domain work-life shock event” in that it simultaneously impacted multiple domains of identification.…”
Section: Introductionmentioning
confidence: 99%